Investments in digital technologies and their return: a macroeconomic analysis ("Journal "U". Economy. Management. Finance.", 2026)
The article presents a macroeconomic analysis of the impact of investments in digital technologies (artificial intelligence, Big Data, IoT) on sectoral productivity. Based on data for 2018–2026, an econometric model reveals the lagged effect of investments in digitalization and differentiation in returns between the service sector and the manufacturing industry.
Keywords: digital technologies; investments; AI; Big Data; labor productivity